Explorando la variabilidad morfométrica del conjunto de camélidos pequeños durante el Arcaico Tardío y el Formativo Temprano en Quebrada Tulán, norte de Chile - Isabel Cartajena Fasting (Revista del Museo de Antropologia, 2009)
Frequently, it is possible to differentiate among large and small size camelids when analysing registers from archaeological sites located at the occidental slope of Puna de Atacama. However, larger animals have received most of the attention having less knowledge about the group of small size camelids. In this paper and by using osteometric methods we study this small size later group. On one hand, we analyse different variables that may affect variability among modern alpacas and vicuñas collections. We focus our work on differences among anterior and posterior phalanxes, inter specific variation and sexual dimorphism. On the other hand, we analyse first phalanxes from Tulán-52 (Late Archaic ca. 4500-3800 BP) and Tulán-54 (Early Formative ca. 3200-2300 BP) characterising their variability through time by comparing current and archaeological samples. Both archaeofaunal assemblages are similar despite their temporal distance. The analyzed specimens correspond to vicuñas denoting the importance of vicuña hunting through time